A bi-level optimization approach for sustainable development and carbon emissions reduction towards construction materials industry: a case study from China. (February 2020) - Xu, Jiuping; Deng, Yawen; Shi, Yi; Huang, Yidan
Highlights: The proposed methodology promotes the sustainability of construction materials. The model maximizes equilibrium between environment and economy. Policy parameters are further optimized to reduce carbon emissions. This paper discusses the impact of uncertainty on results. Case of China's construction material companies shows practicality of this model. Abstract: The production and transportation of some construction materials consume natural resources and energy and emit significant quantities of greenhouse gas. Although many sustainable construction materials have been developed to alleviate these problems, because of the relatively high cost, sustainable construction materials are not yet widely used by construction materials suppliers, which is contrary to many regional authority environmental protection targets. With full consideration of the interests of the regional authorities and construction materials suppliers, this paper developed a Stackelberg equilibrium-based approach to balance economic benefits and carbon emissions reductions. The proposed model was applied to a case from China to demonstrate its effectiveness and practicality in reducing carbon emissions, from which it was found that the model was able to effectively reduce construction materials production and transportation carbon emissions, encourage construction materials suppliers to take environmental initiatives by increasing their production and sales of sustainable products, and assist local authorities achieve their emissions reduction targets. Practical and feasible policy approaches were then given based on the results to assist regional authorities further control construction industry carbon emissions.